Strategies of Dyadic Coping and Self-Regulation in the Family Homes of Chronically Ill Persons: A Qualitative Research Study Using the Emotional Map of the Home Interview Method - Sallay, Viola; Martos, Tamás; Chatfield, Sheryl L.; Dúll, Andrea (Frontiers in Psychology, 2019)
Environmental and emotional self-regulation skills play a critical role in promoting well-being of individuals and in encouraging healthy relationships. However, occurrence of chronic illness in one family member complicates routine dyadic coping processes for the couple. Additionally, according to environmental psychologists, self-regulation processes are influenced by individuals’ perceptions of their socio-physical environments, and during times of chronic illness, the family home is frequently the primary site of dyadic coping. To date, few researchers have investigated the complex relationship among dyadic coping, the family home, and self-regulation processes in the context of chronic illness. The purpose of this paper is to report the results of qualitative research conducted to explore these relationships by analyzing participants’ emotionally significant experiences within the family home. We purposively sampled and conducted in depth semi-structured interviews with 23 adults representing 10 families with one chronically ill adult family member. Representative illnesses included epilepsy (4) and chronic back pain (6). We used the Emotional Map of the Home Interview method (EMHI), an elicitation process in which participants are initially asked to place predefined positive and negative experiences on drawn diagrams of their homes. We analyzed the data through grounded theory coding methods, including open, axial and selective coding. Results of data analysis suggest that the family home operated as a critical socio-physical environment and had a profound impact on environmental and emotional self-regulation as well as on dyadic coping when one partner experienced chronic illness. Key selective codes derived from the data that reflect the variation and nuance within this impact included: “Stress communication through the home space,” “Coping by spatial separation” and “Coping by joint striving for at-homeness.” These results reveal formerly hidden aspects of dyadic coping with chronic illness: the role of environmental cues, represented by the family home in this study, in perceptions of stress; the coordinated use of spatial-environmental contexts to engage the appropriate self-regulatory strategies for coping with illness-related stress. These findings demonstrate the utility of EMHI as an assessment tool and provide meaningful theoretical and practical information about dyadic coping among couples living with chronic disease.